Oldest new Dasypodini (Xenarthra, Cingulata) provides new trails about armadillos evolutionary history. (4th March 2022) - Barasoain, Daniel; González-Ruiz, Laureano; Zurita, Alfredo; Villarroel, Carlos
ABSTRACT: The subfamily Dasypodinae (including Astegotheriini, Stegotheriini and Dasypodini) constitutes the sister group of the remaining diversity of 'armadillos', with an ancient divergence estimated in ca . 40 Ma. (Eocene). Dasypodini represent the only living Dasypodinae, with their oldest records, previous to this contribution, ranging from the middle Miocene ( ca . 12 Ma). Here, we describe a new genus and species of armadillo from the middle Miocene deposits of La Victoria Formation ( ca . 13 Ma, La Venta, Colombia), which represents the oldest known Dasypodini. Remains include an articulated fragment of the dorsal carapace, and the first described cranium of a Miocene Dasypodini. Despite that most of the characters support its inclusion within Dasypodini, its dorsal carapace shows an unique combination of characters from the clades Dasypodini and Euphractinae, allowing to carry out inferences about the transitional morphological processes that took place between both groups. The cladistics analysis corroborates the basal position of this new taxon within Dasypodini, in concordance with its stratigraphic provenance, and reinforces the idea of a tropical origin of the Dasypodini. Finally, the evolutionary history and palaeobiogeography of Dasypodini and Glyptodontinae (large cingulates) show noticeable parallelism, despite the fact that both represent different lineages with evident different ecological characteristics.